Personality style according to the Anikram system and its relationship to the meaning of life among the students of the University of Kufa (Journal of the College of Basic Education, 2022)
The aim of the research is to know the level of the personality pattern according to the engram system for the sample and for each of the three domains, and to find statistically significant differences in the personality pattern according to the engram system among the students of the University of Kufa according to the variables of gender (male - female) and specialization (scientific - human) and (stages). The four academics) universities and each of the three fields. In addition to knowing the level of the meaning of life among the students of the University of Kufa for the sample and finding statistically significant differences in the meaning of life among the students of the University of Kufa according to gender, specialization and the four academic levels. The research was applied to (400) male and female students from the University of Kufa, and to achieve the objectives of the research, the personality style scale and the meaning of life scale were used.